COMMUNICATIVE EFFICIENCY AND/OR COMPREHENSIVE COMMUNICATION: THESES FOR THE TURN - Károly VERESS (Studia Universitatis Babeș-Bolyai. Philosophia, 2016)
My study contains theses related to the three fundamental models of the communication process: the mathematical, the interactional, and the semiotic model, in order to outline the main directions designated by the restructuring of these models under the influence of the turn signalled by the axiom “one cannot not communicate”. The main objective is to present the conditions of possibility and the opportunities of the hermeneutics of communication resulting from the turn.